Training On Marketing Strategies In The Utilization Of Bamboo Creations As A Resource Of Life As Hotel And Culinary Amenities - Juliana Juliana; Ira B Hubner; Sabrina O Sihombing; Rudy Pramono; July Hidayat (CV. AGUSPATI RESEARCH INSTITUTA, 2022)
Bamboo crafts are in demand by foreigners abroad. Sukabumi Regency has bamboo handicrafts that are considered unique and of good quality. There are quite a lot of bamboo craftsmen, but they are constrained by the use of appropriate technology tools (TTG), so they cannot compete with other regions in terms of quality and quantity to be able to penetrate the Asian and European markets. When viewed from the ability of the artisans in Sukabumi Regency, they can make various types of crafts using bamboo materials, including making woven Bamboo. These are the obstacles and problems faced by partners in these limitations and products that are still lacking in the promotion and have not yet received a target market. Therefore, the Community Service team, lecturers at the Faculty of Tourism, Pelita Harapan University, will hold training on marketing strategies in the use of bamboo creations as a source of life for hotel and culinary amenities in collaboration with the Sukabumi bamboo world to provide broad knowledge and insight to the community and bamboo artisans in Egrang Village, Cibiru. , Cicantayan Village, Cicantayan District, Sukabumi Regency. The Community Service Team will train 20 participants on making and using bamboo creations for hotel and culinary amenities and marketing strategies for marketing bamboo creations. The method of community service used is through training in direct mentoring with participants in Sukabumi Regency. The results of this activity are expected to encourage the community to be more active in planting Bamboo, do reforestation with Bamboo, and making the hotel and culinary amenities from bamboo creations which are then sold and developed through the stages of the commercialization process with the application of a marketing mix which includes product development, pricing, distribution channels, and methods Campaign for bamboo products.